The illustrated encyclopedia of extraordinary automobiles - Chapman, Giles (New York DK Pub, 2009)
Describes a variety of automobiles, both production models and prototypes, from the birth of the combustion engine to the present day
Includes index
Keywords: Automobiles -- Miscellanea; Experimental automobiles -- Miscellanea